Inhibition of EGFR autophosphorylation plays an important role in the anti-breast cancer efficacy of the dithiocarbamate derivative TM208 - Ji, Xi-wei; Li, Run-tao; Li, Zai-quan; Li, Liang; Shao, Xue-yan; Wang, Si-yuan; Yuan, Yin; Zhou, Tian-yan; Lu, Wei (Acta pharmacologica Sinica, 2014)
Aim： To investigate the effects of a novel dithiocarbamate derivative TM208 on human breast cancer cells as well as the pharmacoki- netic characteristics of TM208 in human breast cancer xenograft mice. Methods： Human breast cancer MCF-7 and MDA-MB-231 cells were treated with TM208 or a positive control drug tamoxifen. Cell pro- liferation was examined using SRB and colony formation assays. Cell apoptosis was analyzed with Annexin V-FITC/PI staining assay. Protein expression was examined with Western blot, ELISA and immunohistochemical analyses. MCF-7 breast cancer xenograft nude mice were orally administered TM208 （50 or 150 mg.k$1〈1-1） or tamoxifen （50 mg.kgl〈t-~） for 18 d. On d 19, the tumors were collected for analyses. Blood samples were collected from the mice treated with the high dose of TM208, and plasma concentrations of TM208 were measured using LC-MS/MS. Results： Treatment of MCF-7 and MDA-MB-231 cells with TM208 dose-dependently inhibited the cell proliferation and colony formation in vitro （the IC~o values were 36.38＋3.77 and 18.13＋0.76 pmol/L, respectively）. TM208 （20-150pmol/L） dose-dependently induced apoptosis of both the breast cancer cells in vitro. In MCF-7 breast cancer xenograft nude mice, TM208 administration dose-depend- ently reduced the tumor growth, but did not result in the accumulation of TM208 or weight loss. TM208 dose-dependently inhibited the phosphorylation of EGFR and ERK1/2 in both the breast cancer cells in vitro as well as in the MCF-7 xenograft tumor. Conclusion： Inhibition of EGFR autophosphorylation plays an important role in the anticancer effect of TM208 against human breast cancer.